NILAI-NILAI RELIGIUS AKHLAK TASAWUF DALAM NOVEL BUMI CINTA KARYA HABIBUROKHMAN EL-SHAIRAZY - Suci Rahma Wati; Sumiman Udu; Yunus (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
This study aims to analyze the values ​​of Sufism morals in the novel Bumi Cinta by Habiburrahman El-Shairazy. This study uses a literature study. A series of activities related to how to collect library data, reading and research materials in the process. Literature studies can be done with journals, books or other print/digital media related to previous research. The results of the study show that in the Bumi Cinta Novel there are Sufi moral values, including (1) Al-Taubah (Confession and regret for sins), (2) Al-Wara’ (Careful attitude or avoiding matters of subhat), (3) Al-Zuhud (Prioritizing the interests of the afterlife, (4) Al-Sabru (Resistance in facing trials or the nature of accepting fate), (5) Al-Faqir (Sense of need), (6) Al-Tawakal (Submitting matters to Allah, (7) Al-Ridha (Willing or Accepting), (8) Al-Mahabbah (Deep Love), (9) Al-Ma’rifat (Knowing Allah with all your heart).